2017
DOI: 10.1002/glia.23187
|View full text |Cite
|
Sign up to set email alerts
|

Activity‐dependent astrocyte swelling is mediated by pH‐regulating mechanisms

Abstract: During neuronal activity in the mammalian brain, the K released into the synaptic space is initially buffered by the astrocytic compartment. In parallel, the extracellular space (ECS) shrinks, presumably due to astrocytic cell swelling. With the Na /K /2Cl cotransporter and the Kir4.1/AQP4 complex not required for the astrocytic cell swelling in the hippocampus, the molecular mechanisms underlying the activity-dependent ECS shrinkage have remained unresolved. To identify these molecular mechanisms, we employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(89 citation statements)
references
References 105 publications
(206 reference statements)
2
80
1
Order By: Relevance
“…Fluctuations of TMA + /TEA + concentrations under steady-state conditions reflects changes in the volume of the interstitial liquid. Using this type of assay, several groups found that electrical stimulation of neurons causes significant reductions in the extracellular space (cell swelling) in brain preparations from lower vertebrates and mammals [see for example (Svoboda & Sykova, 1991; Jing, Aitken, & Somjen, 1994; Larsen et al, 2014; Larsen & MacAulay, 2017) and comprehensive review by (Sykova & Nicholson, 2008)].…”
Section: Cell Volume Changes During Normal Brain Functioningmentioning
confidence: 99%
See 3 more Smart Citations
“…Fluctuations of TMA + /TEA + concentrations under steady-state conditions reflects changes in the volume of the interstitial liquid. Using this type of assay, several groups found that electrical stimulation of neurons causes significant reductions in the extracellular space (cell swelling) in brain preparations from lower vertebrates and mammals [see for example (Svoboda & Sykova, 1991; Jing, Aitken, & Somjen, 1994; Larsen et al, 2014; Larsen & MacAulay, 2017) and comprehensive review by (Sykova & Nicholson, 2008)].…”
Section: Cell Volume Changes During Normal Brain Functioningmentioning
confidence: 99%
“…12.3C). Moderate elevations in [K + ] o during physiological excitation are thought to be the key reason for the dynamic changes in astrocyte volume in healthy brain tissue [section 12.4, but see alternative view in (Larsen & MacAulay, 2017)]. Work in astrocyte cultures suggests that supraphysiologic increases in [K + ] o (up to 10–15 mM) trigger cell swelling via stimulation of the bumetanide-sensitive NKCC1 (Larsen et al, 2014).…”
Section: A Special Case For Astrocytic Swelling and Cell Volume Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…However, simultaneous changes (e.g., in cell morphology and volume) likely occur for any perturbation of membrane water transport. Experiments with long‐term neuronal activity suppression (AP 5,o plus DNQX o , TTX o , and low [ K o + ]) showed significant cell volume reduction, which might be caused by the reduction in neuronal and glial cell swelling associated with neuronal activity . From Equation , k io (p) is inversely proportional to cell diameter (assuming the cell shape is little changed and P W (p) is constant).…”
Section: Discussionmentioning
confidence: 99%